The Experience of War on the "Enemy Side": Memory Accounts of Galician Soldiers of Francoist’s Army - Galán Ortega, José (Madrygal. Revista de Estudios Gallegos, 2018)
This article examines the war memories of a small groups of Galician intellectuals, composed of Francisco Fernández del Riego, Ramón Piñeiro, Xaime Illa Couto, Elixio Rodríguez y Ramón de Valenzuela (the latter two succeded in deserting and passing to the Republican zone). These men are united by their compulsory incorporation into the Francoist Army, in which they enlisted in order to save themselves from the Fascist repression in their places of birth. The methodological approach is based in cultural history, in a way of seeing, feeling, and thinking the reality expressed by these authors in different texts, relegating the question of authenticity of the contents to secondary importance. It is a question of discerning whether these accounts focus on the soldiers’ experience of war, or, if, on the contrary, they focus on the effect of the war on the soldiers. This article’s conclusions illuminate modes of personal transformation, incomplete emotional trajectories, and fundamentally, the importance of context in the semantic and temporal aspects of writing.
Keywords: Memory; Experience of War; Civil War; Francoist Army; Unwilling Galician Soldiers.